Changes in the racial division of labour during the apartheid era. - Crankshaw, Owen (Journal of Southern African Studies)
Revisits the debate on the dual impact of economic growth and apartheid labor policies on the racial division of labor in the 1970s and 1980s by applying new concepts about the division of labor to South African employment statistics. Conceptualization of occupational groups incorporating neo-Weberian class schemes and labor process theory; Manpower Survey Results.